Dietary Supplementation of Curry (Murraya koenigii) Leaf Powder: Effects on Growth Performance, Nutrient Utilisation and Serum Biochemical Parameters in Crossbred Pigs - Bora, Mondira; Saikia, B.N.; Das, A.K.; Kalita, Dhireswar (Indian Journal of Animal Nutrition, 2018)
Eighteen Hampshire crossbred pigs (Av. BW= of 14.73 kg) irrespective of sex were randomly divided into 3 groups of 6 animals each and feeding trial continued for 80 days. The animals in all the three groups were fed grower ration (BIS, 1992) and curry leaves powder was included at 0, 0.5 and 1.0% level on DM intake basisin groups C, T1 and T2, respectively. The DM intake was similar in 3 groups. The highest average daily gain in body weight was found in group T2. The digestibility coefficient of DM, OM, EE, CF and NFE were similar in 3 groups, however, CP digestibility was better (P